Las armas y las lenguas. Borges y la Gran Guerra - Gersende Camenen (Cuadernos LIRICO)
This article analyses the coincidence of the First World War and Borges’ childhood, considered as two kinds of beginnings, historical and literary. It shows that whereas An Autobiographical Essay suggests, as part of the process of canonization of the writer, that Borges would have felt unconcerned by the conflict, the poems, critics, translations and correspondence of the same period prove, on the contrary, that the Great War was an essential time for the writer, a linguistic and imaginary event which reflects the way children live and understand History. It concludes that wartime’s legacy will be highly significant in Borges’ reflection on language and nation in the 20’s.